Efektivitas Penyaluran Bantuan Kemanusiaan Bagi Korban Bencana Pasca Tsunami Aceh - Teuku Mirza (Magister Administrasi Publik, 2008)
The biggest humanity tragedy in 21st century has been occured on Sunday, December 26th 2004, that is earthquake and tsunami disaster. The impact of this tsunami disaster cause cities of Banda Aceh, Aceh Besar and some regencies/city of Northern and Western Coast of Nangroe Aceh Darussalam got formidable destroy. Communication and public facilities are totally paralyzed. Hundreds thousands people become victims in vain and lost. The data of Bakornas PBP showed that 193 thousands people died, 11 thousand people lost and 37 people got injury. The survivors have to survive, eat and drink any kind of meal during 307 days in the midst of ruins, waste pile, and dead human body. In a week of emergency respon period, central government (Bakornas PBP) and local government (Satkorlak and Satlak PBP) were helped by Indonesian Army-Police and stakeholders struggle to minimize the victims by medical action (first aid) and victim evacuation and to relief victim suffer, public kitchen, sanitation, field hospital and clean water delivery and give acceleration for logistic and medical aid delivery from Jakarta. They are followed by rehabilitation of physical/mental psychological condition of refugee, relocation and reconstruction of infrastructures. For logistic aids, there are many of them in late because of coordination, transportation and mobilization problems (too little heavy vehicle to clear the area, field personnel, fuel and also data, information and communication). This showed that medical and logistic aid distribution for disaster victims were not effective yet that also influenced by the heavy of the disaster impact then the handling was also late.